Let A = {(27)^{-3}⁄9^{-3}}^{1⁄3} We know a^{m}⁄b^{m} = (a⁄b)^{m} ∴ A = {(27⁄9)^{-3}}^{1⁄3} We know (a^{m})^{n} = a^{mn} ∴ A = (27⁄9)^{-3 x 1⁄3} = (27⁄9)^{-1} = (3)^{-1} = 1⁄3. Ans.

Get The Best Grades With the Least Amount of Effort

Here is a collection of proven tips, tools and techniques to turn you into a super-achiever - even if you've never thought of yourself as a "gifted" student.

The secrets will help you absorb, digest and remember large chunks of information quickly and easily so you get the best grades with the least amount of effort.

If you apply what you read from the above collection, you can achieve best grades without giving up your fun, such as TV, surfing the net, playing video games or going out with friends!

Let A = (√32 - √5)^{1⁄3}.(√32 + √5)^{1⁄3} We Know a^{m} x b^{m} = (ab)^{m} ∴ A = {(√32 - √5)(√32 + √5)}^{1⁄3} We Know (a - b)(a + b) = a^{2} - b^{2} ∴ A = {(√32)^{2} - (√5)^{2}}^{1⁄3} We Know (√a)^{2} = a; ∴ A = {32 - 5}^{1⁄3} = (27)^{1⁄3} We know 27 = 3 x 3 x 3 = 3^{3} ∴ A = (3^{3})^{1⁄3} = (3^{3 x 1⁄3}) [since (a^{m})^{n} = a^{mn}] = 3^{1} = 3. Ans.

Solved Example 4 of Negative Exponents

Evaluate : 9^{5⁄2} - 3.4^{0} - (1⁄81)^{-1⁄2}

Solution to Example 4 of Negative Exponents:

Let A = 9^{5⁄2} - 3.(4)^{0} - (1⁄81)^{-1⁄2} We know 9 = 3 x 3 = 3^{2}; (4)^{0} = 1; (1⁄81) = {1⁄(9 x 9)} = {1⁄(9)^{2} } = (9)^{-2}; ∴ A = (3^{2})^{5⁄2} - 3.(1) - (9^{-2})^{-1⁄2} = 3^{2 x 5⁄2} - 3 - (9^{-2 x -1⁄2}) [since (a^{m})^{n} = a^{mn}] = 3^{5} - 3 - (9^{1}) = 3 x 3 x 3 x 3 x 3 - 3 - 9 = 243 - 12 = 231. Ans.

Memory Skills Made Easy : Negative Exponents

Everything we do revolves around strong memory skills that allows us to remember information, no matter how small.

To succeed in any field/endeavour You need to have information at your fingertips.

By improving your memory, you can improve your grades you will get More confidence you will have More control over your daily life.

Here is a resource that Quickly and Easily Improves your Memory.

If (9^{n} x 3^{2} x 3^{n} - 27^{n})⁄(3^{3m} x 2^{3}) = 3^{-3}, Prove that (m - n) = 1.

For Answers, see at the bottom of the page.

Progressive Learning of Math : Negative Exponents

Recently, I have found a series of math curricula (Both Hard Copy and Digital Copy) developed by a Lady Teacher who taught everyone from Pre-K students to doctoral students and who is a Ph.D. in Mathematics Education.

This series is very different and advantageous over many of the traditional books available. These give students tools that other books do not. Other books just give practice. These teach students “tricks” and new ways to think.

These build a student’s new knowledge of concepts from their existing knowledge. These provide many pages of practice that gradually increases in difficulty and provide constant review.

These also provide teachers and parents with lessons on how to work with the child on the concepts.

The series is low to reasonably priced and include